Hybridization and genetic population structure of Alosa population in the United Kingdom. Issue 2 (28th October 2021) - Antognazza, Caterina Maria; Sabatino, Stephen J.; Britton, Robert J.; Hillman, Rob J.; Aprahamian, Miran; Hardouin, Emilie A.; Andreou, Demetra
Abstract: Human‐mediated habitat fragmentation has been proposed as the main factor driving hybridization between the sympatric migratory European shads Alosa alosa and Alosa fallax, which has co‐occurred with substantial population declines in A. alosa . In river systems across Great Britain, shad are negatively affected by navigation weirs constructed in the last 150 years that impede their spawning migrations. Consequently, the aim here was to assess the impact of human disturbances on the genetic introgression and population structure of shad in Great Britain through genotyping 119 Alosa spp. using 24 microsatellite loci.